Magnetite-Functionalized Horse Dung Humic Acid (HDHA) for the Uptake of Toxic Lead(II) from Artificial Wastewater - Rahmat Basuki; Bambang Rusdiarso; Sri Juari Santosa; Dwi Siswanta (Adsorption Science & Technology)
Magnetite-functionalized horse dung humic acid (HDHA) has been successfully prepared by the coprecipitation method, and the as-prepared adsorbent (MHDHA) has been applied as an easy-handling adsorbent for toxic Pb(II) in artificial wastewater. The MHDHA was characterized by Fourier transform-infrared spectroscopy (FT-IR), X-ray powder diffraction (XRD), transmission electron microscopy (TEM), energy dispersive X-ray (EDX), and vibrating sample magnetometer (VSM). The FT-IR study showed that the MHDHA had the characteristics peaks of HA and Fe-O stretching. The XRD analysis revealed that the MHDHA had the 2θ characteristic for magnetite. The TEM image and EDX analysis exhibited that the MHDHA with an average size of ∼14 nm was partially aggregated and contained (w/w) 9.89% carbon, 2.89% nitrogen, and 32.74% oxygen based on functional groups of HDHA. The stability improvement of MHDHA was showed by decreasing HDHA dissolved from 95% to less than 30% at pH 12 after magnetite functionalization. The post-adsorption handling improvement was evidenced by easy and quick retraction by an external magnet with a 62.95 emu/g magnetic strength value. The adsorption capacities were influenced by the pH and ionic strength, whilst the adsorption rates were well simulated by the Ho pseudo-second-order model. The removal uptake of Pb(II) ions increased when the initial concentration was increased and fitted well with the Langmuir isotherm model when the monolayer adsorption capacity was 2.78×10−4 mol/g (equal to 57.64 mg/g). The value of Dubinin-Radushkevich adsorption energy (ED−R) found in this study was 14.78 kJ/mol, which implied that ion exchange is the main mechanism involved in the adsorption process. The regeneration studies of MHDHA show that there was no significant change in composition, morphology, crystallinity, and functional group after five consecutive cycles of the adsorption-desorption process.